Basic rent: Holland, Switzerland, Spain and Canada Experiences - Giudice Baca, Víctor (2015)
Basic Rentis a Governmentpaymenttoeachcityzenor country resident,thatmayensu rebasicneeds: Nutrition, Health,Housing and Education. Basic Personal Rent per month has ben estimated in 650 Euros in Spain, 2000 Euros in Switzerland, 428 Euros in Basque country. Population in poorness in Spain has grown from 23 millions (2007) to 28 millions insixyears (2013). Estimation of poorpopulation in the USA isabout 60 millioncityzens. Several regions of the United States belong already to the Third World. Experiments in Ultrech (Holland) and Dauphin (Canada) are experimentscarriedouttofindoutefectiveness of poornesserradication in Holland and Canada. The European experiments in Finland and Spain are critical. It has been reported a population of 86million of poors in Europe, thatisNine Times more poors than in Peru (9 million).